Does the strengthening of IPRs widen the growth gap? - Seo, Hwan-Joo; Kim, Han Sung; Lee, Young Soo (Technological and Economic Development of Economy, 2015)
This article builds a model of cumulative growth in order to analyze the relationship between intellectual property rights (IPRs) and economic growth in 38 countries from 1980 to 2005. The analysis focuses on the impacts of IPRs on the growth gap between countries using a catch-up model and USPTO database. The empirical results show that the strengthening of IPRs has a positive impact on innovation in developed and developing countries in Asia, while we fail to find evidence in Latin America. Secondly, similar to assertions made by De Long and Summers (1991) and Dowrick and Nguyen (1989), investment in fixed capital plays a critical role in growth gap dynamics. What needs to be emphasized here is the cumulative causal relationship between investment and growth: investment in fixed capital improves productivity and encourages economic growth thereby triggering even more investment. This paper confirms that the strengthening of IPRs and investment in fixed capital contribute to the widening of the economic development gap for the 1980–2005 period.